Effectiveness of ginger (zingiber officinale) phytotherapy in reducing premenstrual syndrome severity among adolescent girls: A quasi-experimental controlled study - Suriani Bahrun; Muhammad Basir; Salmah Arafah; Kamriana Kamriana; Mantasia Mantasia (Jurnal Ilmiah Kesehatan Sandi Husada, 2026)
Introduction: Premenstrual syndrome (PMS) is a prevalent condition among adolescent girls, characterized by physical, emotional, and behavioral symptoms that may impair daily functioning and quality of life. Despite its high prevalence, evidence on comprehensive, non-pharmacological interventions targeting PMS in adolescents, particularly in school-based settings, remains limited. This study aimed to evaluate the effectiveness of ginger phytotherapy in reducing PMS severity among adolescent girls. Research Methodology: A quantitative pre-experimental study with a one-group pretest–posttest design was conducted at SMP Negeri 3 Makassar, Indonesia, between January and February 2026. A total of 50 participants were recruited through purposive sampling, of whom 46 completed the study. PMS severity was assessed using DSM-IV-TR–based criteria before and after intervention. Participants received ginger decoction 2–3 times daily for 7 days before menstruation, following a standardized protocol. Data were analyzed using descriptive statistics and the Wilcoxon signed-rank test, with effect size calculated. Multivariate analysis was performed using ordinal logistic regression. Statistical significance was set at α = 0.05. Results: There was a significant reduction in PMS severity following the intervention (Z = −2.81, p = 0.005; r = 0.41). The proportion of participants with mild PMS increased from 10.9% to 78.3%, while the proportion with severe PMS decreased from 10.9% to 0%. Multivariate analysis showed that ginger phytotherapy significantly reduced the likelihood of higher PMS severity (OR = 0.16; 95% CI: 0.04–0.58; p = 0.006). Conclusion: Ginger phytotherapy is an effective and feasible non-pharmacological intervention for reducing PMS severity among adolescents. Its integration into school-based health programs may support menstrual health management in resource-limited settings.